2019
DOI: 10.1016/j.forsciint.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the forensic clinical examination on the judicial assessment of rape complaints – developments and trends

Abstract: Highlights  The Prosecution Service found a forensic clinical examination of the victim important for the legal process in 49% of cases of sexual assault.  A forensic examination of the perpetrator is associated with laying of charges and a guilty verdict.  The decision not to prosecute was significantly more often aided by the forensic examination of victim and/or perpetrator in cases of 'conflicting explanations', uncooperative victims and if the perpetrator denied intercourse.  The prosecution services'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Of the total 124 cases, 22 % was described as stranger rape. A similar percentage was found in other comparable, retrospective cohort studies 2,10,22,23 and in Heinskou (2017) questionnaire based-survey 19 , but it is lower than the 30% found in Boesen Pedersen (2018) questionnaire-based survey. 4 Other retrospective cohort studies reports a higher prevalence of stranger rapes 6,[24][25][26] Overall, the cohort studies vary in time and setting.…”
Section: Discussionsupporting
confidence: 86%
“…Of the total 124 cases, 22 % was described as stranger rape. A similar percentage was found in other comparable, retrospective cohort studies 2,10,22,23 and in Heinskou (2017) questionnaire based-survey 19 , but it is lower than the 30% found in Boesen Pedersen (2018) questionnaire-based survey. 4 Other retrospective cohort studies reports a higher prevalence of stranger rapes 6,[24][25][26] Overall, the cohort studies vary in time and setting.…”
Section: Discussionsupporting
confidence: 86%
“…High-quality forensic documentation can facilitate increased investigation, prosecution, and conviction rates for survivors of sexual violence [ 8 10 ], yet no validated, published tools are available to assess the quality of documentation after sexual assault. To our knowledge, this is the first peer-reviewed study to develop a validated quality-assessment tool for sexual assault documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Timely and high-quality forensic medical examination, evidence collection, and documentation are all part of comprehensive care for survivors of sexual violence and are crucial to ensuring survivors of SGBV can access justice [11]. High-quality documentation of the clinical exam after sexual assault has been shown to increase trial, prosecution, and conviction rates of perpetrators [12][13][14][15]. A South African study analyzed the association of sexual assault injury documentation and legal outcomes and found that conviction was more likely when cases had documented injuries [16].…”
Section: Introductionmentioning
confidence: 99%